A NONINVASIVE MOLECULAR APPROACH: EXPLOITING SPECIES-LOCUS-SPECIFIC PCR PRIMERS IN DEFEATING NUMTS AND DNA CROSS-CONTAMINATION OF CERCOPITHECIDAE - M. A. B. Abdul-Latiff; N. R. Aifat; S. Yaakop; B. M. Md-Zain1 (Journal of Animal and Plant Sciences, 2017)
The lack of a standardized, noninvasive molecular approach to studying genetic aspects of primates has made it hard for primatologists to decode the evolutionary history of these species. Researchers must optimize their own techniques to fully exploit the available samples. Lack of species-locus-specific primers also contributes to difficulties in using noninvasive genetic samples. Thus, the objectives of this study were to develop a standardized technique to collecting samples noninvasively, propose newly designed species-locus-specific primers, and optimize conditions for polymerase chain reaction (PCR) for Macaca fascicularis, M. nemestrina, Trachypithecus cristatus, and T. obscurus. Nine new species-locus-specific primers for three different loci of mitochondrial DNA, namely D-loop, cytochrome oxidase subunit I (COI), and cytochrome b, were successfully designed. These primers proved to be efficient in amplifying larger datasets (up to ~1,000 bp) of the targeted species in the optimized PCR conditions. The species-locus-specific primers are able to anneal to host DNA alone in highly contaminated feces of highlighted species. They can also offer alternatives measures in avoiding contamination related to nuclear insertion of mitochondrial pseudogenes (numts).
Keywords: Noninvasive; species-locus-specific primers; numts; Macaca; Trachypithecus